The response of Irisin Serum and insulin resistance to acute Pilates training sessions Pilates Training in obese sedentary women - Rezvan Kheirandish; Rouhollah Ranjbar; Ali Veisi (Fasa University of Medical Sciences, 2018)
Background & Objective: Irisin is myokine, that is secreted by acute exercise activity from the muscle and increases energy consumption. The purpose of this study was to determine the response of irisin serum and insulin resistance to acute pilates training sessions pilates training in obese sedentary women. Materials & Methods: This research is a semi experimental study with pre-and post-test design. The statistical population of this study was made up of disabled obese women in Ahwaz, with 21 subjects (mean age 39.1±10.0 years and BMI 35.9±3.4 kg/m2) were randomly divided into Pilates group (n=12) and control group (n=9). The training group performed 60-minute Pilates training with a14-16 Borg perceived perception index, while the control group did not exercise. After at least 8 hours-fasting, blood samples were collected before and immediately after each activity, to measure the levels of Irisin, glucose, insulin and insulin resistance. Data were analyzed with paired-sample t-test and ANCOVA and the relationship between the variables was calculated by Pearson correlation test. Results: The results indicated no significant changes in blood glucose, insulin, insulin resistance index and serum Irisin levels in Pilate's group compared with the control group after a Pilates exercise session (p≥0.05). Furthermore, correlation was not between Irisin to, glucose, insulin, and insulin resistance index (p≥0.05). Conclusion: Although research on this regard is a beginning pathway. However, Acute Pilates exercise does not seem to have an effect on glucose, insulin, insulin resistance, and Irisin level.